Nutritionsensitive food systems: options for interventions. - Kauffmann, Domitille. (Tufts University. Tisch Library., 2017)
In the context of the SDGs and UN Decade of Action for Nutrition, governments and development partners are increasing their commitment to make agriculture and food system policies and programmes "nutrition-sensitive". A prominent challenge for transforming this commitment into action is the limited capacity to design, implement and monitor nutritionsensitive food and agriculture policies and programmes. FAO has been working to address these capacity gaps at country and regional levels and capitalized on these experiences in consultation with many partners to develop a Toolkit and e-learning modules for policy and programme planners on Nutrition-sensitive Agriculture and Food Systems. These resources were introduced through a fun and interactive session.